Laser gingivectomy for maintaining periodontal health in fixed orthodontic patients: a systematic review - Zeballos, Blacker Kevin Caracela (2024)
Objective: This systematic review evaluates the effect of laser gingivectomy on the improvement of periodontal health parameters in patients with gingival enlargement due to fixed orthodontic appliances. Materials and methods: A systematic review was conducted in 3 databases without language or date restrictions. Clinical trials involving patients with gingival enlargement (GE) or hyperplasia induced by fixed orthodontic treatment and treated by laser gingivectomy, conventional surgery (scalpel) or non-surgical periodontal treatment (NSPT) were included regarding periodontal parameters such as bleeding on probing, probing depth, gingival inflammation, among others. Results: From the 363 articles initially retrieved, only 6 were included after evaluation of the full text. However, all studies were considered to have a high risk of bias. It was detected that periodontal parameters (bleeding on probing, probing depth, gingival inflammation) were significantly lower in the laser-treated group when compared to NSPT. No statistically significant differences were observed between the use of laser or scalpel; however, the laser group offered faster healing and reduced postoperative complications. Conclusions: Within the limitations of this systematic review, the adjunctive use of laser gingivectomy to NSPT, for the treatment of GE induced by fixed orthodontic treatment offers favorable clinical results in the improvement of periodontal health parameters. In addition, it offers faster healing, less bleeding, less gingival swelling and postoperative pain, and better comfort for the patient compared with conventional surgery. Clinical relevance: The use of laser as an adjunct to NSPT proves to be a favorable and more comfortable option not only to treat GE but also to maintain periodontal health in patients with fixed orthodontics.